Incidence of fungal diseases on leaves of apricot and plum cultivars in Hungary - Holb, I. J.; Drén, G.; Thurzó, S.; Erdős, Z.; Soltész, M.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2007)
In this two-year study, incidence of Polystigma rubrum on plum, and Apiognomonia erytrostoma on apricot were evaluated on several stone fruit cultivars in Hungary. Results showed that most apricot cultivars expressed symptoms caused by A. erytrostoma, graded between 2 and 3 (10-50%) by the end of the summer in 2005 and 2006. The most tolerant apricot cultivars were Budapest and Mandulakajszi while the most susceptible ones were ’Magyar kajszi’ and ’Piroska’. Assessments made on plum showed that most of the plum cultivars were tolerant or lowly susceptible to P. rubrum such as ’Ageni’, ’Althann ringló’, ’Bluefre’, ’Cacanska najbolja’, ’Silvia’, ’Ruth Gerstetter’, ’Tuleu gras’ and ’Utility’. The most susceptible plum cultivars to P. rubrum were ’Besztercei clones’ and ’Debreceni Muskotály’.